Dinamika penghindaran pajak perusahaan: Menelaah pengaruh koneksi politik, kepemilikan institusional dan komisaris independen - Sulistyowati, Sulistyowati; Chusnah, Flourien Nurul; Supriati, Diana; Rusli, Devvy; Pohan, Tassya Aulya (Jurnal Manajemen, 2024)
This study aimed to examine the influence of political connections, institutional ownership, and independent commissioners on Tax Avoidance. The research was conducted on pharmaceutical sub-sector companies on the Indonesia Stock Exchange (IDX). This study used a quantitative approach to descriptive research, which was measured using multiple linear regression-based methods with Eviews 12. The population of this study is pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. The sample in this study was determined based on the purposive sampling method, with a total sample of 8 pharmaceutical sub-sector companies, so the total observations in this study were 40 observations. The data used in this study is secondary data. Data collection techniques use documentation methods through IDX's official website, www.idx.co.id, and literature study methods derived from accounting journal sources, books, and literature, as well as hypothesis testing using t-tests. The results proved that Political Connections did not affect Tax Avoidance, Institutional Ownership did not affect Tax Avoidance, and Independent Commissioners affected Tax Avoidance.